INHERITANCE RIGHTS OF OUTSIDE MARRIAGE DESCENDANTS AFTER THE RULING OF THE CONSTITUTIONAL COURT NUMBER 46 OF 2010 - Adawiyah, Rodiatun; Prasetyo, Muhammad Arif; Ongko , Eric; Wibowo, Stefani; Kamal, Julius (IBLAM LAW REVIEW, 2024)
Humans were created by God to consist of men and women, therefore they are required to live in pairs in a bond called marriage. As stated in the 1945 Constitution, Article 28B Paragraph (1), which reads "Everyone has the right to form a family and continue their offspring through legal marriage". Before there were special regulations regarding marriage, in particular Indonesia still used the Civil Code (KUHPerdata) or Burgerlijk Wetboek (BW) as stated in Book One, Chapter IV concerning Marriage. The research method used in this research is normative juridical, which is supported by primary and secondary data sources, and qualitative analysis is carried out. The research results show that in the Civil Code, children outside of marriage have the status of illegitimate children of their parents. However, the Civil Code provides an opportunity for both parents to recognize the child as a legitimate child. Article 42 of the marriage law. If the marriage is invalid, then the children born from the marriage do not occupy the position of legitimate children. Constitutional Court Decision Number 46/PUU-VIII/2010 only recognizes children resulting from religiously valid marriages. Apart from that (the result of adultery), legally the child has no blood relationship with his father, but only has a civil relationship. If the biological father is not responsible, then the child through the mother can sue the father in civil law. The regulation of the inheritance rights of illegitimate children in Indonesian legislation and after the issuance of the Constitutional Court Decision Number 46/PUU-VIII/2010 can be concluded in Article 863 B.W. First part Regarding the inheritance share of illegitimate children in group I, if the testator dies leaving legitimate descendants and/or the husband/wife who lives the longest, then illegitimate children who can be recognized as inheriting a third of what they would have received had they been legitimate child. Then Article 100 KHI states that children born out of wedlock only have a lineage relationship with their mother and their mother's family. Then article 43 paragraph 1 of Law Number 1 of 1974 states that children born outside of marriage only have a civil relationship with their mother and their mother's family.